ANALISIS TERHADAP FUNGSI BAHASA INDONESIA HUKUM DALAM MEWUJUDKAN KEPASTIAN HUKUM - Wika Yudha Shanty (University of Merdeka Malang, 2016)
Indonesian law is a part of the Indonesian language that has a specificity in the diction and the wording. Indonesian law is not only used by the legal community, especially the legal scholars, but also by the whole society. Implementation of legal language is not only found in legislation, but also in other legal products in law enforcement. Indonesian law is used in legislation, requisition, Polidori, lawsuit, answer, replica, uplink, decision and so on. The practical aspects of law enforcement by judges, prosecutors, advocates, notaries, police, legal journalists. Student law and others. Law is a grand design that is used as a means of control and communication within the community. The movement and work of the law for interaction and communication within the community, in order to improve the quality of life and prevent conflict, should be communicated through the language for the purpose and purpose of law for the enforcement and legal certainty until the community is always maintained its regularity. Indonesian law must be continuously improved in quality, to prevent multiple interpretations or different interpretations. It aims at the upholding of legal certainty, which becomes one among other legal functions such as justice and legal benefit.